GOT2: New therapeutic target in pancreatic cancer - Jiarui Bu; Zeyu Miao; Qing Yang (Genes and Diseases)
In recent years, the incidence and mortality rates of pancreatic cancer have been steadily increasing, and conventional therapies have shown a high degree of tolerance. Therefore, the search for new therapeutic targets remains a key issue in current research. Mitochondrial glutamic-oxaloacetic transaminase 2 (GOT2) is an important component of the malate-aspartate shuttle system, which plays an important role in the maintenance of cellular redox balance and amino acid metabolism, and has the potential to become a promising target for anti-cancer therapy. In this paper, we will elaborate on the metabolic and immune effects of GOT2 in pancreatic cancer based on existing studies, with a view to opening up new avenues for the treatment of pancreatic cancer.